A simplified zero‐voltage switching detection circuit and switching loss dynamic optimisation method for synchronous buck converter - Sizhao Lu (Wiley, 2021)
Abstract This letter proposes a simplified zero‐voltage switching (ZVS) detection circuit and switching loss dynamic optimisation method. The proposed circuit and tuning method can automatically adjust the switching frequency of a synchronous buck converter to work in critical current mode to realise ZVS under a wide load range. The advantages of the proposed circuit and method are that ZVS detection and switching loss dynamic optimisation can be realised by only one ZVS detection circuit, which simplifies the detection circuit, further improves the power density and reduces the number of analogue‐to‐digital conversion channels of the digital signal processor. A prototype of the synchronous buck converter with a rated input voltage of 100 V is established to verify the effectiveness of the proposed ZVS detection circuit and switching loss dynamic optimisation method. By using the proposed detection circuit and optimisation method, the switching loss of the MOSFETs has been greatly reduced and an efficiency improvement of nearly 1% at peak output power has also been achieved.